(untitled) (Research, Society and Development, 2021)
Binge Eating Disorder is one of the fastest growing eating disorders worldwide. It is defined by eating high amounts of food in a short period of time, followed by feelings of guilt and discomfort. BED is related to several psychological disorders, including anxiety and depression. Anxiety is characterized by an excessive preoccupation with an event in an exaggerated manner, which may be associated with fear with physical symptoms. Depression is identified by depressed mood, change in appetite, change in weight, guilt and thoughts of death. The main objective of the present study was to evaluate the relationship between binge eating and psychological disorders of anxiety and depression in women. This is a cross-sectional and descriptive study. Data collection was applied with 93 women, aged between 20 and 50 years, living in the regions of Águas Claras and Guará, online, through Google Forms, with validated questionnaires such as the Periodic Compulsion Scale and the Hospital Scale of anxiety and depression. The research resulted in a relationship between BED and anxiety and depression (30.6%) and showed that even without this relationship of disorders, there was a high number of women with indicators for psychological disorders (69.4%). A multidisciplinary follow-up is essential for both disorders, emphasizing the professional nutritionist for BED, so that they act directly in the treatment and recovery of the individual’s nutritional status.